2005
DOI: 10.1080/02688690500305548
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous presentation of meningiomas with other intracranial tumours

Abstract: Fifteen patients with simultaneous presentation of meningiomas with other intracranial tumours are reviewed. The associated tumours included a brain metastasis in six cases, glioma in three, pituitary adenoma in two, craniopharyngioma in one,acoustic schwannoma in two and brain lymphoma in one. A correct preoperative radiological diagnosis was made in 12 patients; in three others the associated tumour was discovered at operation and by histological studies. A one-stage removal of both tumours through the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
54
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 28 publications
0
54
0
Order By: Relevance
“…Meningiomas are the tumour type more often found in cases of multiple intracranial tumours of different histology in humans (Spallone et al, 1991;Davis et al, 1995;Maiuri et al, 2005). This is due both to the frequent occurrence of even incidental intracranial meningiomas and to their long clinical evolution before diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Meningiomas are the tumour type more often found in cases of multiple intracranial tumours of different histology in humans (Spallone et al, 1991;Davis et al, 1995;Maiuri et al, 2005). This is due both to the frequent occurrence of even incidental intracranial meningiomas and to their long clinical evolution before diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…This is due both to the frequent occurrence of even incidental intracranial meningiomas and to their long clinical evolution before diagnosis. Thus, they have an increased probability of simultaneously harbouring another primary or secondary tumour (Maiuri et al, 2005). In a recent review of meningiomas associated with other tumours of different origin in humans, authors observed that the most frequent combinations were those of meningioma and brain metastasis, meningioma and glioma, and meningioma and pituitary adenoma (Maiuri et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations